Infarct volume after glioblastoma surgery as an independent prognostic factor - Bette, Stefanie (Oncotarget, 2016)
Postoperative ischemia is associated with reduced functional independence measured by karnofsky performance score (KPS), which correlates well with overall survival. Other studies suggest that postoperative hypoxia might initiate infiltrative tumor growth. Therefore, aim of this study was to analyze the impact of infarct volume on overall survival and progression free survival (PFS) of glioblastoma patients. 251 patients with surgery for a newly diagnosed glioblastoma (WHO IV) were retrospectively assessed. Pre- and postoperative KPS, date of death/last follow-up and histopathological markers were recorded. Pre- and postoperative tumor volume and the volume of postoperative infarction were manually segmented. A significant correlation of infarct volume with postoperative KPS decrease (P = 0.001) was observed. Infarct volume showed a significant impact on overall survival (P = 0.014), but not on PFS (P = 0.112) in univariate analysis. This effect increased in the subgroup of patients with near-total tumor resection (> 90%) (overall survival: P = 0.006, PFS: P = 0.066). Infarct volume remained as an independent prognostic factor for overall survival in multivariate analysis (HR 1.013 [1.000–1.026], P = 0.042) including other prognostic factors (age, extent of resection, postoperative KPS). Postoperative infarct volume significantly correlates as an independent factor with overall survival after glioblastoma surgery. Besides the influence of perioperative infarction on postoperative KPS, postoperative hypoxia might also have an effect on tumor biology initiating infiltrative growth and therefore impaired survival.